Navigating Risks In Ar-Rahnu Cooperatives Exploration Of Risks Typologies And Management Strategies - Nor Fadilah Bahari; Zurina Shafii; Mustafa Mohammad Hanefah; Nuzul Akhtar Baharudin (UIS Press, 2026)
Indexed by MYCITE